Participation and forest protected areas in Chile: Insights from Mapuche and peasant communities - Guillermo Pacheco Habert; Alejandro Mora-Motta; Till Stellmacher; Francisco Ther-Ríos (University of Bonn, Center for Development Research (ZEF), 2023)
There are multiple approaches to forest conservation, including public and private protected area initiatives and varying degrees of involvement of local communities. At present, protected areas are seldom managed by local communities under integrated sustainable approaches. This research provides insights into the modes of participation of Mapuche and peasant communities in the planning and management of forest protected areas in two municipalities of Los Ríos Region in southern Chile. Indeed, being directly related to the land, the forest, and the sea, the way of life of Mapuche and peasant communities in southern Chile constitutes an excellent case to elaborate on the constitution of borders, limits and frontiers generated by forest protected areas, and at the same time to glimpse possible strategies for their participatory planning and management. The paper is based on two in-depth empirical field works carried out between 2013 and 2019 using participatory observation, field notes and interviews. In the municipality of Panguipulli, in the Andean cordillera, we focus on participation of Mapuche and peasant communities in the Villarrica National Park, the MochoChoshuenco National Reserve and the Huilo-Huilo Private Reserve. In the municipality of La Unión, in the coastal cordillera, we address the participation of Mapuche and peasant communities in the Alerce Costero National Park and the private Coastal Valdivian Reserve. The findings show that community participation mechanisms are generally consultative in the public protected areas of both municipalities, which effectively allows for a top-down implementation of territorial decision-making. Decisions are concentrated with the state authorities that manage the protected areas and with the owners of the private reserves. The formal consultative participation mechanisms in the public protected areas do not include a comprehensive participation of the Mapuche and peasant communities living adjacent to the areas. In the case of private protected areas, there are participation mechanisms for Mapuche and peasant communities, however, mainly limited to capacity building and employment. The lack of participation in decision-making is associated with open questions of land ownership and so-called 'green grabbing' in rural and indigenous ancestral territories in Chile, where both private actors and state authorities appropriate parts of nature by structuring spatial and sociocultural borders. Finally, it is concluded that it is necessary that state authorities provide more effective and transparent participation mechanisms in both private and public protected areas that guarantee meaningful and decision-making participation schemes.
Keywords: 330; Participation; conservation; borders; Mapuche; peasant communities; Chile